In planta comparative transcriptomics of host-adapted strains of Ralstonia solanacearum - Ailloud,Florent; Lowe,Tiffany M.; Robène,Isabelle; Cruveiller,Stéphane; Allen,Caitilyn; Prior,Philippe (PeerJ, 2016)
Background. Ralstonia solanacearum is an economically important plant pathogen with an unusually large host range. The Moko (banana) and NPB (not pathogenic to banana) strain groups are closely related but are adapted to distinct hosts. Previous comparative genomics studies uncovered very few differences that could account for the host range difference between these pathotypes. To better understand the basis of this host specificity, we used RNAseq to profile the transcriptomes of an R. solanacearum Moko strain and an NPB strain under in vitro and in planta conditions. Results. RNAs were sequenced from bacteria grown in rich and minimal media, and from bacteria extracted from mid-stage infected tomato, banana and melon plants. We computed differential expression between each pair of conditions to identify constitutive and host-specific gene expression differences between Moko and NPB. We found that type III secreted effectors were globally up-regulated upon plant cell contact in the NPB strain compared with the Moko strain. Genes encoding siderophore biosynthesis and nitrogen assimilation genes were highly up-regulated in the NPB strain during melon pathogenesis, while denitrification genes were up-regulated in the Moko strain during banana pathogenesis. The relatively lower expression of oxidases and the denitrification pathway during banana pathogenesis suggests that R. solanacearum experiences higher oxygen levels in banana pseudostems than in tomato or melon xylem. Conclusions. This study provides the first report of differential gene expression associated with host range variation. Despite minimal genomic divergence, the pathogenesis of Moko and NPB strains is characterized by striking differences in expression of virulence- and metabolism-related genes.
Keywords: Ralstonia solanacearum; Transcriptomics; Host adaptation